Penerapan Metode Six Sigma Define, Measure, Analyze, Improve And Control (DMAIC) Untuk Mengurangi Produk Cacat pada Proses Pembuatan Pagar Minimalis di PT. XYZ - Putra, Ramadhani Cahyono; Widya, Adi Rusdi; Maulidani, Bagas Caesar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The high rate of defective products in the production process of minimalist fences at PT. XYZ negatively affects both quality and production efficiency. This study aims to identify the most frequent types of defects and apply the Six Sigma method using the DMAIC (Define, Measure, Analyze, Improve, Control) approach. Data were collected through direct observation, interviews, and production documentation from January to December 2024. The findings reveal that uneven welding and incorrect dimensions are the most common defects. Root causes include human factors, non-standardized methods, machine conditions, and the working environment. Improvements were carried out through SOP development, technical training, measuring tool calibration scheduling, and workflow reorganization. Post-implementation evaluation showed a 52.6% decrease in defective products, an increase in sigma level from 3.41 to 4.10, and a 10% boost in production efficiency. The DMAIC approach has proven effective in enhancing product quality and achieving a more controlled and standardized production process.